Student Self-Efficacy and Aptitude to Participate in Relation to Perceived Functioning and Achievement in Students in Secondary School With and Without Disabilities - Bertills, Karin; Granlund, Mats; Augustine, Lilly (Frontiers in Psychology, 2021)
School-based Physical Education (PE) is important, especially to students with disabilities whose participation in physical activities out of school is limited. The development over time of participation-related constructs in relation to student perceived functioning and achievement is explored. Students in mainstream inclusive secondary school self-rated their PE-specific self-efficacy, general school self-efficacy, aptitude to participate in PE and perceived physical and socio-cognitive functional skills at two timepoints, year 7 and year 9. Results were compared between three groups of students with: disabilities (n=28), high grades (n=47), or low grades (n=30) in PE. Over time perceived physical skills of students with disabilities became strongly associated with self-efficacy and aptitude to participate. Perceived socio-cognitive skills in the study sample improved and had positive effect on PE-specific self-efficacy. Efforts should be made to limit the accelerated negative impact of perceived restricted functioning of students with disabilities. Grading criteria need to be developed to comply with standards adapted to fit abilities of students with disabilities. Meaningful learning experiences appear to be created when participation is promoted, and capacity beliefs (PE-specific self-efficacy) are boosted. Allocating resources to support the development of student socio-cognitive skills seem to have potential for overall positive school outcome.